Effect of Kulattha Guda with and without Virechana Karma in the Management of Tamaka Shwasa (Bronchial Asthma) - Babita Meena; Rashmi Mutha; Ajay Kumar Sahu (Journal of Ayurveda, 2023)
Introduction: Tamaka Shwasa is a type of Shwasa Roga with Vata-Kapha predominance originating from Pittasthana. Tamak Shwasa can be correlated with modern entity bronchial asthma due to its similarity in signs and symptoms and causative factors. The aim of the study is to compare the efficacy of Kulattha Guda with or without Virechana Karma in the management of Tamaka Shwasa. Methods: A total of 30 patients of Tamaka Shwasa (bronchial asthma) were selected based on the signs and symptoms and randomly divided into two groups. Group A – Kulattha Guda after Virechana Karma in a dose of 10 g twice a day orally for 30 days with lukewarm water. Group B – Kulattha Guda in a dose of 10 g twice a day orally for 30 days with lukewarm water. Results: In Group A, the subjective parameters such as Shwasakricchata, Kasa, Pratishyaya, Nidralpata, Ghurghurakam, and Anxiety Control Questionnaire (ACQ) score showed percentage-wise relief as of 75.68%, 76.67%, 75%, 75%, 78.57%, and 72.20%, respectively, and in Group B, percentage-wise relief was found in Shwasakricchata, Kasa, Ghurghurakam, and in ACQ score as of 70.59%, 72.22%, 70%, and 66.92%, respectively. In Group A, objective parameters such as peak expiratory flow rate (PEFR) and forced expiratory volume 1 s (FEV1) had shown highly significant results with giving an improvement of 59.09% and 59.64%, respectively, and in Group B, percentage-wise relief was found in PEFR and FEV1 as of 54% and 52.63%, respectively. Results obtained were statistically significant. Conclusion: The trial drug was found effective and well tolerated to the patient. Kulattha Guda was administered after Virechan Karma was found more effective.